Morphological evaluations of human gingival fibroblasts exposed to novel dental adhesives in combination with glucocorticoids or dihydropridines - biomed 2013 - Garner, Angelia D; Tucci, Michelle A; Benghuzzi, Hamed A (Biomedical sciences instrumentation, 2013)
The present study evaluated the morphology of human gingival fibroblasts when exposed to dental adhesives in combination with glucocorticoids or dihydropridines in an in vitro environment. The cultured gingival fibroblasts used were obtained from the American Type Culture Collection (ATCC). The three dental adhesives used were Polymethyl methacrylate, OptiBond®, and Prime & Bond®. The glucocorticoid of choice was Cortisol along with the dihydropridine (Nifedipine). Fibroblasts were treated with each bonding agent, Cortisol, or Nifedipine for durations of 24, 48, and 72 hours. Morphological evaluation revealed that at 24 and 48 hour phases, there were no observable differences between the control and groups exposed to a combination of an adhesive and Cortisol. However, at 72 hours the cells exposed to combinations of OptiBond® with Cortisol and Prime & Bond® with Cortisol displayed predominantly spindle shaped cells compared to the predominantly round cells observed in the other samples. Cells exposed to a combination of adhesives with Nifedipine at 24 hour phase did not display any significant morphological alterations. In contrast, cells exposed to Prime & Bond® in combination with Nifedipine at the 48 hour phase revealed occasional morphological changes compared to control group. Likewise and at the end of 72 hour phase, the OptiBond®/Nifedipine and Prime & Bond®/Nifedipine groups displayed morphological differences such as clustering compared to the control. Biochemical analysis determined that there was a significant difference among the groups exposed to adhesives with Cortisol at 48 (P<0.002) and 72 hours (P <0.001). Glutathione (GSH) and Malondialdehyde levels (MDA) indicated that there were significant differences in the metabolic activities in groups exposed to combinations of dental adhesives and Cortisol at all phases. There were no differences in lactate dehydrogenase (LDH) levels among the groups exposed to combinations of adhesives and Cortisol or adhesives and Nifedipine. It is concluded that there were minor structural (morphological) alterations and major functional (biomarkers) changes observed upon exposing the gingival fibroblasts in combinations with Cortisol (stress environment) or Nifedipine.